Dendritic cell‐derived thrombospondin‐1 is critical for the generation of the ocular surface Th17 response to desiccating stress. Issue 6 (27th August 2013) - Gandhi, Niral B.; Su, Zhitao; Zhang, Xiaobo; Volpe, Eugene A.; Pelegrino, Flavia S. A.; Rahman, Salman A.; Li, De‐Quan; Pflugfelder, Stephen C.; de Paiva, Cintia S.
Abstract : TSP‐1‐positive DCs promote the Th‐17 immune response in the eye, after exposure to desiccating surface stress. Abstract : TSP‐1 is a physiologic activator of TGF‐β, a critical induction factor for Th17‐mediated immunity. The purpose of this study was to investigate the role of TSP‐1 in the induction of the Th17 ocular surface response to DS. TSP‐1KO and WT mice were subjected to DS5 and DS10), and parameters of ocular surface disease, including corneal barrier function, conjunctival CD4 + T cell infiltration, and GC density, were evaluated. TSP‐1KO mice subjected to DS had less corneal barrier disruption, reduced loss of PAS+ GC, and decreased CD4 + T cell infiltration in the conjunctiva. In contrast to WT, TSP‐1KO mice failed to up‐regulate MMP‐3 and MMP‐9 mRNA transcripts in the cornea and IL‐17A mRNA transcripts in the conjunctiva. RAG‐1KO recipients of adoptively transferred CD4 + T cells isolated from TSP‐1KO mice subjected to DS5 showed milder dry‐eye phenotype and less conjunctival inflammation than recipients of CD4 + T cells from DS5 WT control. Reconstitution of TSP‐1KO mice with WT DCs prior to DS reversed the resistance of the TSP‐1KO to DS‐induced immunopathology. In conclusion, DC‐derived TSP‐1 is critical for generating the Th17 ocular surface response to DS.